Calculation of the non forward scattering amplitude for long range potentials. - Garibotti, C. R.; Grinstein, F. F.; Miraglia, J. E. (Springer-Verlag, 1980)
Fil: Garibotti, C. R. Comisión Nacional de Energía Atómica; Argentina